Challenges and problems modern ecotoxicology faces - Filipova, Margarita (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Analyses have been carried out of the basic and specific objectives and priorities of ecotoxi-cology, its tendencies and differences from toxicology. Proposals have been expressed to include new groups of potential contaminants of the biosphere as an object of study by the ecotoxicology.